2011
DOI: 10.1152/ajplung.00118.2010
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic release of the receptor for advanced glycation end products from in vitro and in situ alveolar epithelial cells

Abstract: Although the receptor for advanced glycation end products (RAGE) has been used as a biological marker of alveolar epithelial cell injury in clinical studies, the mechanism for release of soluble RAGE from lung epithelial cells has not been well studied. Therefore, these studies were designed to determine the mechanism for release of soluble RAGE after lipopolysaccharide (LPS) challenge. For these purposes, alveolar epithelial cells from rat lungs were cultured on Transwell inserts, and LPS was added to the api… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 44 publications
(45 reference statements)
2
32
0
1
Order By: Relevance
“…Specifically, RAGE labeling appeared more intensely stained in odontoblasts of pulpitis versus healthy tissue. RAGE expression by odontoblasts appears comparable to that reported for alveolar epithelial cells [56], synovial fibroblasts [38], and in the pathogenesis of lung injury in mice [54, 57] in which RAGE is expressed at low levels in normal tissues and in the vasculature and becomes upregulated at other sites where its ligands accumulate [19]. Previous studies show that odontoblasts express receptors for LPS, TLR-2, and TLR-4 on the cell membrane [3, 58].…”
Section: Discussionsupporting
confidence: 72%
“…Specifically, RAGE labeling appeared more intensely stained in odontoblasts of pulpitis versus healthy tissue. RAGE expression by odontoblasts appears comparable to that reported for alveolar epithelial cells [56], synovial fibroblasts [38], and in the pathogenesis of lung injury in mice [54, 57] in which RAGE is expressed at low levels in normal tissues and in the vasculature and becomes upregulated at other sites where its ligands accumulate [19]. Previous studies show that odontoblasts express receptors for LPS, TLR-2, and TLR-4 on the cell membrane [3, 58].…”
Section: Discussionsupporting
confidence: 72%
“…Epithelial-mesenchymal transition (EMT), resident lung fibroblast migration, proliferation, transdifferentiation into myofibroblasts, and fibrocyte recruitment take place in the fibroproliferative phase of ALI (25). Receptor for advanced glycation end products (RAGE), which has a role in alveolar epithelial cell spreading and adherence, when impaired, mediates an increase in cell migration and proliferation (28,84,90,262). It has been now revealed that, whereas under basal conditions RAGE is linked to the cytoskeleton by interacting with the family of ezrin/radixin/moesin (ERM), in the presence of inflammatory cytokines this interaction is disrupted by ERM phosphorylation and subsequent ERM interaction with CD44 and actin stress fibers, causing loss of adhesion and an invasive phenotype contributing to EMT (22).…”
Section: Fibroproliferative Phase and Repair Alimentioning
confidence: 99%
“…A reduced alveolar expression of RAGE is related to pathophysiological changes of the lung tissue, such as carcinoma (3), fibrosis (34,37), and chronic obstructive pulmonary disease (COPD) (34). In addition to the membrane-bound receptor, soluble RAGE (sRAGE) forms exist as the result of either alternative splicing (22) or protein shedding by metalloproteinases (39,52). sRAGE normally exists in the bronchoalveolar lavage (BAL) at a high level (53), but it is deficient in neutrophilic asthma and COPD (47,49).…”
mentioning
confidence: 99%